What motivates smallholder farmers to adapt to climate change? Insights from smallholder cropping in far-western Nepal. (December 2022) - Lamichhane, Prahlad; Miller, Kelly K.; Hadjikakou, Michalis; Bryan, Brett A.
Abstract: Adaptation to climatic change in smallholder agriculture is pivotal to ensuring food security in many developing countries. Research into adaptation to climate change in smallholder agriculture has often used capital-based indicator frameworks, with only limited consideration of the cognitive dimensions influencing adaptation motivation. In this study, we interviewed 327 farmers in far-western Nepal and the responses were used in structural equation modelling to quantify determinants of adaptation motivation. Results indicate that farmers with a higher level of adaptation appraisal are motivated to adapt, whereas the higher level of threat appraisal exhibited a weak influence. Social drivers such as incentives and subjective norms had a weak effect. Risk experience influenced adaptation motivation negatively. Adaptation cost was negatively related to the adaptation appraisal. Determinants of adaptation motivation varied across agroecosystems. These results suggest that effective adaptation policies must emphasise on the factors that positively contribute to adaptation motivation (e.g., adaptation efficacy) and target interventions that break down the barriers to adaptation (e.g., adaptation cost), while boosting trust and confidence in farmers to adaptation measures. Findings can inform adaptation policies in similar smallholder contexts of Asia/South Asia, while the research approach can be used to generate insights into farmers' adaptation motivation globally. Graphical Abstract: ga1 Highlights: Smallholder farmers urgently need to adapt to climate change. Self-efficacy, knowledge, confidence in adaptation measures motivated adoption. Perceived climate risk had a weak influence on adaptation and cost was a barrier. Drivers of adaptation motivation varied between agroecosystems. Agricultural policies need to target behavioural drivers to motivate adaptation.